Effective Leadership and Management in Nursing (Eighth Edition) - Sullivan, Eleanor J. (Pearson, 2020)
Extensively updated to reflect the latest changes in the healthcare system, this book will help both practicing and student nurses manage successfully in today's challenging, resource-limited healthcare environments.